Experimental sociology outline of a scientific field - Barrera, Davide 1968- (Cambridge University Press, 2025)
Experiments have gained prominence in sociology in recent years. Increased interest in testing causal theories through experimental designs has ignited a debate about which experimental designs can facilitate scientific progress in sociology. This book discusses the implications of research interests for the design of experiments, identifies points of commonality and disagreement among the different perspectives within sociology, and elaborates on the rationales of each. It helps experimental sociologists find appropriate designs for answering specific research questions while alerting them to the challenges. Offering more than just a guide, this book explores both the historical roots of experimental sociology and the cutting-edge techniques of rigorous sociology. It concludes with a tantalizing peek into the future and provides a roadmap to the exciting prospects and uncharted territories of experimental sociology
Title from publisher's bibliographic system (viewed on 22 Nov 2024)
Keywords: Sociology / Experiments; Sociology / Methodology; Experimental design; Social sciences / Experiments